English English - Auliya, Dewi Nur; Al Umami, Habiba (UIN Alauddin Makassar, 2024)
This research aims to examine how Indonesian netizens of X consider physical bullying in wider scope, which is social media (cyber-world) through X. Researchers analyze traditional bullying that occurs in Indonesia but is used as discourse on social media (cyber). Therefore a netizen attitude assessment system appears in comments and posts, especially those related to affect, assessment, and appreciation. The method used in this research is Qualitative research under Discourse Analysis methods, with the social media data source